2013
DOI: 10.1039/c3ay41011k
|View full text |Cite
|
Sign up to set email alerts
|

Simple and rapid removal of the interference in gangliosides extracted from HPTLC spot on MALDI-TOF MS analysis

Abstract: Extraction of thin-layer chromatography (TLC) spot with organic solvents is one of the convenient methods for glycolipid isolation from crude samples, but other background contaminants are also co-extracted during this process. Calcium sulfate (gypsum), starch and synthetic polymers are commonly used as binders in TLC plates, and the co-extracted synthetic polymers usually interfere with further structural analyses, especially in analysis by mass spectrometry (MS). Several column chromatographic processes are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
1
5
0
Order By: Relevance
“…To suppress the background peaks in TLC-blot MSI, the removal of binders on the TLC plate would be required before blotting. In a previous study, we confirmed that DCE could remove the background from glycolipids scraped and recovered from the TLC plate [27][28][29] . We applied this method to remove the background from the TLC plate.…”
Section: Removing Of Background Peak From Fixing Agent Of Silica Gelsupporting
confidence: 72%
See 1 more Smart Citation
“…To suppress the background peaks in TLC-blot MSI, the removal of binders on the TLC plate would be required before blotting. In a previous study, we confirmed that DCE could remove the background from glycolipids scraped and recovered from the TLC plate [27][28][29] . We applied this method to remove the background from the TLC plate.…”
Section: Removing Of Background Peak From Fixing Agent Of Silica Gelsupporting
confidence: 72%
“…3A). Generally, calcium sulfate (gypsum), starch and synthetic polymers are used as binders in TLC plates; therefore, they are transferred to the PVDF membrane together as we described before 29 . To suppress the background peaks in TLC-blot MSI, the removal of binders on the TLC plate would be required before blotting.…”
Section: Removing Of Background Peak From Fixing Agent Of Silica Gelmentioning
confidence: 99%
“…Calcium sulfate (gypsum), starch and synthetic polymers are commonly found as contaminants in GSL samples obtained by solvent extraction from TLC plates. In order to remove these contaminants, Kamimiya et al () have dried extracts (from chloroform/methanol/water) in a glass tube and simply washed several times with the non‐polar solvent, 1,2‐dichloroethane.…”
Section: Studies On Specific Carbohydrate Typesmentioning
confidence: 99%
“…Among organic revealing agents (Figure 1), orcinol (5-methylbenzene-1,3-diol) allows selective detection of sugar groups in GSL, PL, GL to be performed. [48,49] Lipids without sugar units give no response when using orcinol at 550 nm.…”
Section: Organic Revealing Agentsmentioning
confidence: 99%